1993
DOI: 10.1557/jmr.1993.2149
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of Bi2Sr2CaCu2Oy and Bi2Sr1.75Ca0.25CuOy

Abstract: The solidification processes for the compositions Bi 2 Sr 2 CaCu 2 O y (2212) and Bi 2 Sr 1.75 Ca 0.25 CuO y (2201) were determined as a function of oxygen partial pressure. During solidification in argon, the superconducting phases were generally not observed to form for either composition. The solidification processes for the compositions Bi2Sr2CaCu20y (2212) and Bi2Sri.75Cao.25CuOy (2201) were determined as a function of oxygen partial pressure. During solidification in argon, the superconducting phases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For doped compounds, the process is further complicated by additional elements in the Bi-Sr-Ca-Cu-O system which may cause the growth of additional phases during partial melting. Partial melting and solidification of Bi 2 Sr 2 CaCu 2 O y strongly depends on processing parameters such as maximum melting temperature, time of reaction and solidification rate [13]. The partial oxygen pressure also affects the reaction kinetics during partial melting and phase growth [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For doped compounds, the process is further complicated by additional elements in the Bi-Sr-Ca-Cu-O system which may cause the growth of additional phases during partial melting. Partial melting and solidification of Bi 2 Sr 2 CaCu 2 O y strongly depends on processing parameters such as maximum melting temperature, time of reaction and solidification rate [13]. The partial oxygen pressure also affects the reaction kinetics during partial melting and phase growth [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…13 Little information is available about the amount and distribution of the intergrowths within the grains. In general, their amount was found to be increased in samples of Bi-rich starting compositions.13 Furthermore, they are frequently found at twin boundaries, and their insertion is thought to be a possible mechanism for solid-state diffusion parallel to the c-axis.9 Lang et aln reported that the alternate arrangement of the half-cells of 2201 and 2212 is slightly preferred; only few identical half-cells are nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some results about the phase decomposition of Bi 2 Sr 2 CaCu 2 O y polycrystal samples [8][9][10] but single crystals can be used more readily to clarify some of this issue since they have less impure phase, crystal grain and other crystal defects. As pointed out by some authors of our group [11,12] the Bi 2 Sr 2 CaCu 2 O y crystal is ready to decompose when annealed in air at temperatures above 450 • C and the segregated phases, including Bi oxides, Bi x Sr y Ca z oxide and Bi 2 Sr 2 CuO x (Bi2201), are located on the surface of the annealed crystal sheets.…”
Section: Introductionmentioning
confidence: 99%